Will EGFRvIII and neuronal-derived EGFR be targets for imipramine? - Li, Zesheng; Wang, Bo; Wu, Jianjian; Han, Lei (Frontiers in Pharmacology, 2023)
Tricyclic antidepressant (TCA) is an old and well-established therapeutic agent with a good safety profile, making them an excellent candidate for repurposing. In light of the growing understanding of the importance of nerves in the development and progression of cancer, attention is now being turned to using nerve-targeting drugs for the treatment of cancer, particularly TCAs. However, the specific mechanism by which antidepressants affect the tumor microenvironment of glioblastoma multiforme (GBM) is still unclear. Here, we combined bulk RNA sequencing, network pharmacology, single-cell sequencing, molecular docking and molecular dynamics simulation to explore the potential molecular mechanism of imipramine in the treatment of GBM. We first revealed that the imipramine treatment is presumed to target EGFRvIII and neuronal-derived EGFR, which may play a pivotal role in treating GBM by reducing the GABAergic synapse and vesicle-mediated release and other processes thereby modulating immune function. The novel pharmacological mechanisms might provide further research directions.